159k views
0 votes
Using separation of variables, solve the differential equation dB/dt = -k(B-24) for B

B(0)=28

User Roy Cohen
by
4.9k points

1 Answer

3 votes

Answer:


B(t) = 4\, e^(-k \cdot t) + 24.

There isn't enough information to determine the value of
k. It is thus treated as a non-zero constant. (In case that
k = 0,
B(t) = 28.)

Explanation:

Start by separating the two differentials,
dB and
dt. Multiply both sides of this equation by the denominator
dt to obtain


dB = - k (B -24) \, dt.

Separate the variables. Move all terms that involve
B to the side with
dB; move all terms that involve
t to the side with
dt.

Divide both sides with
(B - 24) assuming that it is not equal to zero.


\displaystyle (1)/(B - 24) \,dB = -k \, dt.

Note that the first derivative of
(B - 24) with respect to
B is just
1. Hence, leaving the constant
(-k) on the side with
dt could potentially simplify the calculations.

Integrate both sides.


\displaystyle \int (1)/(B - 24)\, dB = \int -k \, dt.

The left-hand side is similar to the first-derivative of a logarithm with
e as its base.
(d)/(du) \ln |u| = (1)/(u).

Apply
u-substitution to the denominator
(B - 24). Let
u = B - 24. Then
du = dB since the expression
(B - 24) is linear with a coefficient of
1.


\displaystyle \int (1)/(B - 24)\, dB = \int (1)/(u)\, du = \ln |u| = \ln |B - 24|.

The given condition
B(0) = 28 implies that
B - 24 > 0.

The right-hand side is constant. Only linear expressions can produce a first-derivative of a constant.
\displaystyle \int -k\, dt = (-k) \int dt = -k\, t.

Hence
\ln (B - 24) = -k \, t + C.

The constant
C only needs to appear on one side of the equation.


\ln(x) is the inverse of
e^x. Hence
e^(\ln (B - 24)) = B - 24. Place both sides of the equation as the exponent of
e:


e^(\ln (B - 24)) = e^(-k \, t + C).


B - 24 = e^(-k \, t) \cdot e^(C).

Apply the given initial condition of
t = 0 and
B = 28 to find the value of
e^(C):

  • Left-hand side:
    28 - 24 = 4.
  • Right-hand side:
    e^(-k \, t)\cdot e^(C) = e^(0) \cdot C = C.

Hence
C = 4. Add
24 to both sides of the equation to obtain


B = 4 e^(-k \, t) + 24.

Apparently, the value of
B is dependent on that of
t. Hence the function expression:


B(t) = 4 e^(-k \, t) + 24.

User SunChero
by
4.8k points